2011
DOI: 10.1002/jso.21933
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic‐assisted microwave ablation for hepatocellular carcinoma: Safety and efficacy in comparison with radiofrequency ablation

Abstract: Lap-MWA is a safe and efficacious locoregional therapy for HCC which achieves outcomes comparable to Lap-RFA. Shorter operative times were realized with this modality and complete coagulative necrosis was confirmed histologically on explanted livers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 18 publications
0
91
0
Order By: Relevance
“…These findings indicate that despite a patient population of mainly cirrhotic individuals, operative MWA can be performed safely. This is underscored by multiple other series again highlighting the safety and effectiveness of operative MWA (14)(15)(16). Most important from this series, we evaluate our current results in comparison to our previously reported outcomes in 2013 (8).…”
Section: Discussionmentioning
confidence: 77%
“…These findings indicate that despite a patient population of mainly cirrhotic individuals, operative MWA can be performed safely. This is underscored by multiple other series again highlighting the safety and effectiveness of operative MWA (14)(15)(16). Most important from this series, we evaluate our current results in comparison to our previously reported outcomes in 2013 (8).…”
Section: Discussionmentioning
confidence: 77%
“…Although several studies have reported better diseasefree survival and a lower frequency of recurrence after surgical resection compared to RFA [10,11] , others report better overall survival and disease-free survival for HCC patients with multi-nodular tumours following RFA [12] . Recently, Simo et al [13] reported no difference regarding the efficacies of MWA and RFA procedures. TACE is routinely performed on HCC patients who are not eligible for surgical resection or tumour ablation techniques.…”
Section: Hepatocellular Carcinoma and The Unmet Medical Needsmentioning
confidence: 99%
“…The authors considered a high probability of long-term survival of patients with a single lesion ≤4.0 cm in maximum diameter and Child-Pugh class A cirrhosis. Numerous studies have compared MWA with RFA for treating HCC and found similar disease-free survival, cumulative survival, and complication rates in the two groups [68,69,70,71,72,73,74]. However, so far, only one RCT [68] has compared the efficacy of MWA with that of RFA, in a series of 72 patients (36 RFA/36 MWA) with equivalent background demographics and mean tumor sizes.…”
Section: Local Ablative Therapymentioning
confidence: 99%